EVALUASI TATA CARA PENILAIAN UNTUK PTPN XII (PERSERO) BERDASARKAN KEP-100/MBU/2002 - Lilis Ardini (EKUITAS (Jurnal Ekonomi dan Keuangan), 2008)
The objective of this research is to get the descriptive in depth and effectiveness of performance appraisal system (based on financial account, operational account, and administrative account) that has been implemented by PT Perkebunan Nusaniara XII (Pcrsero) based on the Badan Usaha Milik Ncgara of Minister Decree, Number: KEP-100/MBU/2002.  This research used qualitative research with single case study and multiple unit analysis approach. The study involved 6 respondents as unit managers and as assistant of unit manager. They are financial manager, plant manager, accounting manager, processing manager, strategic business unit manager, strategic business manager, and  assistant of financial manager. This study concluded that the performance appraisal system that has been implemented by PT Perkebunan Nusantara XII (Persero) was not effective in practice. This was caused by the differences of PT Perkebunan Nusantara XII (Persero) core business whose  long time plants and harvest for  many years from cultivation. It is suggested that the productivity is the main resource to increase as well as to improve performance and the sustainability of PT Perkebunan Nusantara XII (Persero)